A Comparison of Reinforcement Planning for Basement Wall Shelter Based on SS EN 1990: 2008 (2015) with Technical Requirements for Household Shelter 2023 - Fenia Hayatun Nikmah; Usmanul Hayadi Umar (Journal of Civil Engineering and Planning (JCEP), 2023)
Singapore is an example that applies the concept of household housing, namely buildings that are used as evacuation places. One of the buildings that applies the household residential concept is a detached type of residential house with a basement located at 102 Jalan Langgar Bedok, Bedok Planning Area, Singapore in an HDB housing block. The technical guidebook used as a guideline for building household shelters is "2023 Household Shelter Technical Requirements". The aim of this research is to compare household reinforcement shelter planning based on SS EN 1990: 2008 (2015) with the 2023 Household Shelter Technical Requirements. The method used in this research is a quantitative method using secondary data, namely the dimensions of the household shelter building and the results on-site survey. The results of this research show that when planning reinforcement using SS EN 1990: 2008 (2015), the diameter of the reinforcement used is larger, namely H16-100, compared to the 2023 Household Shelter Technical Requirements guidebook, namely H10-100. This is because the walls of household shelters are also used as basement walls.